The Tendency of Faculty Members to the Organizational Culture based on Denison Model: A Case Study of Kunduz University - Sadry, Abdul Mahmood; Zeerak, Shokrullah; Popalzai, Wahida Yaqobi (Technium Education and Humanities, 2022)
The organizational culture is the dominant pattern of beliefs, feelings, and norms that people believe in and, as a guide, follow in their behavior. The main purpose of this study was to investigate the tendency of faculty members to an organizational culture based on Denison’s organizational culture model at Kunduz University, which was implemented by descriptive method. The data collection tool was denison’s organizational culture questionnaire, the validity of which was determined through content research and surveys of three high-ranking professors, and its reliability was calculated by calculating the Cronbach’s Alpha coefficient for organizational culture (0.82), which was reliable. The statistical population of this study includes all professors of Kunduz University who were selected by simple random sampling method with 95% confidence level and 5% error to 102 persons. The data obtained from the questionnaires were analyzed using Excel and IBM SPSS-24 software. The results showed that the degree of dominance of organizational culture in all four dimensions of Denison’s model is lower than average p <a = 0.052 = 0.00 = 0.00 = 0.01 <0.05. A as result; the faculty members of Kunduz University have a lower than average tendency towards Denison’s organizational culture model, and this has the same effect on the professors of this university due to gender differences.